The Role of Married Women's Work in the Socialization of Children: A Field Study in the City of Bani Walid - Ezuldeen Abdulsalam Mohammed Ahmed, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The current study aimed to identify the role of married women's work in the process of socializing children, focusing on how working mothers balance professional responsibilities and their fundamental role in raising children. The study followed the descriptive analytical method, utilizing a questionnaire as the primary tool for data collection, which was distributed to a sample of working mothers in the city of Bani Walid. The theoretical framework addressed the concept of socialization and its primary agents, while the field study analyzed the impact of maternal absence during working hours on children's behavior and academic achievement. The results indicated that while work contributes to improving the family's economic level and enhancing the mother's personality, it imposes significant pressures that may affect the time allocated for direct interaction with children. The study found that most working mothers face challenges in reconciling household duties and job requirements, which sometimes leads to reliance on alternative socialization agents such as grandmothers or nurseries. However, the results also showed that a mother's work can promote values of independence and responsibility in children if managed effectively. The study recommended the necessity of providing support systems for working women, such as nursery centers within workplaces, and reducing working hours for mothers of young children to ensure a balance between professional contribution and the quality of the socialization process.
Keywords: Married Women's Work; Socialization; Children; Working Mother; Social Environment